Microsurgical anatomy of the cisternal anterior choroidal artery with special emphasis on the preoptic and postoptic subdivisions - TANRIÖVER, Necmettin; Kucukyuruk, Baris; ULU, Mustafa Onur; İŞLER, Cihan; Sam, Bulent; Abuzayed, Bashar; Uzan, Mustafa; Ak, Halil; Tuzgen, Saffet (My University, 2014)
Object. The object of this study was to delineate the microsurgical anatomy of the cisternal segment of the anterior choroidal artery (AChA). The authors also propose a new classification of this segment on the basis of its complicated course within the carotid. and crural cisterns in relation to important neurovascular structures, and the site of origin, course, and areas of supply of perforating arteries.